BC Hydro Ground Motion Prediction Equations for Subduction Earthquakes. Issue 1 (February 2016) - Abrahamson, Norman; Gregor, Nicholas; Addo, Kofi
An updated ground motion prediction equation (GMPE) for the horizontal component response spectral values from subduction zone earthquakes is developed using a global data set that includes 2, 590 recordings from 63 slab earthquakes (5.0 ≤M ≤7.9) and 953 recordings from 43 interface earthquakes (6.0 ≤M ≤8.4) at distances up to 300 km. The empirical data constrain the moment magnitude scaling up toM 8.0. ForM > 8.0, a break in magnitude scaling is included in the model based on the magnitude scaling found in numerical simulations for interface earthquakes in Cascadia. The focal depth scaling of the short-period spectral values are strong for slab earthquakes, but it is not seen for interface events. The distance scaling is different for sites located in the forearc and backarc regions, with much steeper attenuation for backarc sites. The site is classified by V S 30 with constrained nonlinear site amplification effects.